S70 Diagnostic utility and prognostic value of quantitative cardiac MR indices in patients with suspected pulmonary hypertension. (2nd December 2011) - Swift, A J; Rajaram, S; Condliffe, R; Capener, D; Hill, C; Davies, C; Hurdman, J; Elliot, C; Wild, J M; Kiely, D G
Abstract : Introduction and Objectives: The aim of this study was to assess the clinical utility of quantitative MR indices of cardiac morphology and function in a large cohort of patients with pulmonary hypertension (PH). Methods: We retrospectively studied 233 consecutive patients with suspected PH who underwent cardiac MRI and right heart catheterisation (RHC) within 48 h. Four chamber and short axis (SA) CINE images were acquired using cardiac gated multi-slice imaging with a steady state free precession sequence at 1.5T. The diagnostic and prognostic significance of quantitative measurements of right ventricular morphology and function were assessed. Results: Right ventricular end-diastolic mass index was the measurement with the strongest correlation with mPAP (r=0.74) and the highest diagnostic accuracy for the detection of PH (area under the receiver operator curve of 0.91). During the mean follow-up of 18 months (0–36 months), 36 patients with PH died. Right ventricular ejection fraction (p=0.003), right ventricular stroke volume index (p=0.03) and IVC size (p=0.01) were the MR predictors of mortality across the subgroups of PH. MR measurements of right ventricular ejection fraction (p=0.004), right ventricular stroke volume index (p=0.02), and left ventricular diastolic eccentricity index (p=0.005), all predicted mortality in patients with pulmonary arterial hypertension, Abstract S70 figure 1 below shows the Kaplan–Meier plots the MR predictors of mortality in PAH. IVC size (p=0.018) was an independent predictor of mortality in the full cohort of patients with PH, and diastolic eccentricity index (p=0.037) was an independent predictor of adverse outcome in patients with PAH. Conclusion: Cardiac MRI provides a comprehensive assessment of right ventricular morphology and function in patients with PH. This study confirms the diagnostic and prognostic applicability of MRI in unselected patients with PH of varied aetiologies in a practical clinical setting.